CONCEPTUAL REFLECTION OF THE CHANGE OF STATE EXPORT POLICY IN THE DEVELOPMENT STRATEGY (International Journal of Economic Integration and Regional Competitiveness, 2024)
The article highlights the reasons for the conceptual understanding of the changing role of the state export policy in the development strategy of New Uzbekistan. The features and tasks of applying its effective tools and methods are described on the basis of mastering the world practice of effective foreign economic activity and the experience of modern trends in the export promotion mechanism.